The impact of Callisto's atmosphere on its plasma interaction with the Jovian magnetosphere. Issue 11 (12th November 2015) - Liuzzo, Lucas; Feyerabend, Moritz; Simon, Sven; Motschmann, Uwe
Abstract: The interaction between Callisto's atmosphere and ionosphere with the surrounding magnetospheric environment is analyzed by applying a hybrid simulation code, in which the ions are treated as particles and the electrons are treated as a fluid. Callisto is unique among the Galilean satellites in its interaction with the ambient magnetospheric plasma as the gyroradii of the impinging plasma and pickup ions are large compared to the size of the moon. A kinetic representation of the ions is therefore mandatory to adequately describe the resulting asymmetries in the electromagnetic fields and the deflection of the plasma flow near Callisto. Multiple model runs are performed at various distances of the moon to the center of Jupiter's magnetospheric current sheet, with differing angles between the corotational plasma flow and the ionizing solar radiation. When Callisto is embedded in the Jovian current sheet, magnetic perturbations due to the plasma interaction are more than twice the strength of the background field and may therefore obscure any magnetic signal generated via induction in a subsurface ocean. The magnetic field perturbations generated by Callisto's ionospheric interaction are very similar at different orbital positions of the moon, demonstrating that local time is only of minor importance when disentangling magnetic signals generated by the magnetosphere‐ionosphere interaction from those driven by induction. Our simulations also suggest that deflection of the magnetospheric plasma around the moon cannot alone explain the density enhancement of 2 orders of magnitude measured in Callisto's wake during Galileo flybys. However, through inclusion of an ionosphere surrounding Callisto, modeled densities in the wake are consistent with in situ measurements. Key Points: Callisto's atmosphere/ionosphere is important in the Moon's interaction with Jupiter's magnetosphere Magnetic signals driven by the magnetosphere‐ionosphere interaction can obscure induction signals Callisto's pickup tail is flat and asymmetric, driven by large gyroradii of ionospheric pickup ions